Sistem Informasi Pengelolaan Alat Laboratorium (SIP Alat Lab) di SMK 1 Sigli - Famiah; Idwan, Harry; Ihsanuddin (Jurnal Manajemen Sistem Informasi (JMASIF), 2024)
The Laboratory Equipment Management Information System (SIP Alat Lab) at SMK 1 Sigli aims to enhance efficiency and accuracy in managing laboratory tools. Previously, equipment management was conducted manually, which posed risks such as recording errors, equipment loss, and irregular maintenance. This study designs and develops a computer-based system to streamline the recording, borrowing, and maintenance of laboratory equipment. SIP Alat Lab integrates various functions, including equipment data recording, equipment condition monitoring, and usage report generation, allowing laboratory managers to handle resources more effectively. The research includes the system design phase, database creation, and system implementation in the SMK 1 Sigli laboratory. The findings indicate that the developed system accelerates administrative processes, reduces equipment loss, and improves overall equipment maintenance. System users, including laboratory staff and teachers, have provided positive feedback regarding its ease of use and the efficiency it brings. It is anticipated that this system can be adapted by other schools to improve the quality of laboratory equipment management.